Analyzing the Role of Rainbow Card in Improving EFL Students’ Reading Comprehension through Descriptive Text - Mufliha, Wilda Nur; Margana, Margana; Abidin, M. Zaenal; Robbaniyah, Inayatur; Ridho, M. Zainul; Malisa, Malisa; Fitriani, Lina Ulfa; Andika, Jeffri Dian (JOLLT Journal of Languages and Language Teaching, 2024)
The development of reading comprehension is an important skill that helps students with a variety of academic assignments. It facilitates their ability to comprehend textual information and to analyze, clarify, and articulate their own opinions about them. Consequently, students are required to strengthen their comprehension of textual content through the academic assignments that their teachers provide. One of reading comprehension’s main goals is to help students become better readers by helping them understand texts properly. This research aim was to analyze the role of rainbow card strategy in efl learning context by emphasizing reading ability. The method of this study was mixed method with a classroom action research design adopted from Kemmis & M. Taggard. The participant of this research was studentâ€™s eighth grade students consist of 30 students. The data collection was in form of observation, written test, and interview for both students and a teacher. The findings of this study indicated that appropriate reading strategies such as rainbow card technique play an important role in enhancing the reading comprehension abilities of EFL students.. A further result was also described in cycle two and three in which significantly improved studentsâ€™ comprehension. Nonetheless, in the first of cycle, the statistical data indicated low improvement due to the limited time and new approach. At the same time, a new innovation and approach in pedagogy was needed in order to improve the learning and teaching outcomes. Finally, the research emphasized the significance of adopting innovative pedagogical practices to cultivate a more engaging and impactful learning due to the limitation of the studentsâ€™ interest and comprehension in reading.